Ethical and political implications in 99 Cahaya di Langit Eropa as a travel literature - Mashlihatin, Anis (Diksi, 2022)
This study aims to show the hidden agenda in the 99 Cahaya di Langit Eropa as a travel literature. The method used is divided into two, namely data collection methods and data analysis methods. The data in this study are in the form of statements about the content, nature, characteristics, condition of something or symptoms, or statements about the relationships between something and something else. Data analysis methods used in this study are historical methods, comparisons, and logical inference. This research shows that the 99 Cahaya di Langit Eropa has ethical and political implications which are the fundamental agenda in travel stories. The ethical implications of this novel are first, by demeaning Indonesia, this novel follows the ethical violations committed by Western orientalism. Second, by demeaning the West, this novel also commits the same ethical violation, namely demeaning other nations. The political implication of this novel is an attempt to free oneself from the hegemony of colonial orientalism, to elevate the dignity of the colonized nation. The answer to liberation offered to Indonesia is a typical answer given by Indonesian Muslim scholars, namely by making Indonesia an Islamic country that is Western and Islamic West. Indonesia is understood as a nation that still must be westernized and at the same time Muslimized.Keywords: ethical implications, political implications, travel literature, West, Islam